Going forward and beyond: on the track of a practice turn in supply chain sustainability studies - Raphael Lissillour; Minelle E. Silva (RAUSP Management Journal)
Purpose – Despite the growing interest in the field of supply chain sustainability (SCS), little exploration of new theories exists. Therefore, this paper aims to introduce practice theories to SCS studies through a practice turn. Design/methodology/approach – This is a conceptual paper in nature. Hence, based on theoretical arguments, the authors elaborate on how the practice turn can arise in the SCS field. Findings – The theoretical elaboration is rooted in the understanding that sustainability is not limited to the materiality of environmental and social issues, as often observed. Instead, there is a need to include immaterial, emotional and intangible elements to better comprehend SCS practice. The authors argue that a continuum exists for a practice turn, including practice-based view, practice-based studies and critical practice theory. Research limitations/implications – The authors provide a research agenda with a comprehensive perspective of understanding the application and implications of practice theories to SCS. Practical implications – The practice turn in SCS studies can support managers to better understand their practices not only through recognizing explicit activities but also mainly by reflecting on hidden elements that affect their performance. Social implications – SCS studies can better engage with grand challenges through a practice turn, which helps increase its contribution to solving social problems. Originality/value – Unlike previous literature, the paper elaborates on how practice theories are powerful in supporting both scholars and practitioners in moving away from an extremely economic focus to genuinely embrace sustainability practice. In doing so, the practice turn appears as an important phase for SCS field maturity.